2019
DOI: 10.1080/02670836.2019.1645389
|View full text |Cite
|
Sign up to set email alerts
|

Improved properties of Ti-6Al-4V by combining isothermal equal-channel angular processing and hot-extrusion

Abstract: The aim of this work was to study effects of hot extrusion on the microstructure of Ti-6Al-4V (wt-%) alloy processed by ECAP. Firstly, an isothermally Ti–6Al–4V alloy processed by Equal channel angular pressing(ECAP) was preheated at 950°C for 6 min and then hot extruded at 900°C. The hot extrusion minimised the grain size and maximised the mechanical strength. Therefore, it was demonstrated that hot extrusion of Ti-6Al-4V alloys that processed by ECAP could be performed without compromising any mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…According to the grain size distribution of Post-ECAP samples, the proportion of grains with sizes of less than 1 µm is more than 50%. Studies have shown that the ultra-fine grain materials with uniform and stable microstructure can be prepared by a method combining large plastic deformation and deformation heat treatment [ 35 , 36 ]. The grains of Post-ECAP samples had been refined by multi-pass ECAP [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the grain size distribution of Post-ECAP samples, the proportion of grains with sizes of less than 1 µm is more than 50%. Studies have shown that the ultra-fine grain materials with uniform and stable microstructure can be prepared by a method combining large plastic deformation and deformation heat treatment [ 35 , 36 ]. The grains of Post-ECAP samples had been refined by multi-pass ECAP [ 26 ].…”
Section: Discussionmentioning
confidence: 99%